A oferta de disciplinas humanistas no ensino médico do Brasil - Merigo, Francini Lima (2014)
In Brazil, in spite of humanism is an old topic in the history of medicine, including his medical education in Brazil is recent, officially legalized in Resolution CNE/CES in 4 of 7 November 2001, the Ministry of Education, National Council of education/Board of Higher education, which includes the National Curriculum Guidelines for Undergraduate Medical. However, the Ministry of Health have questioned as to the graduates listing, in relation to the supply of the health needs of the population. Given that there is urgency to appropriate and effective measures in vocational training, it is necessary to understand the aspects for improvement in the comprehensive care and more comprehensive information on medical education. In this light, the present study aims to describe and analyze the provision of humanistic disciplines in medical education in Brazil. For this, we carried out a descriptiveanalytic research with documented reference base, with qualitative and quantitative approach. The data analyzed was collected through the curriculum matrices, searched through information disseminated on the Internet by HEIs. The sample was composed of subjects of Humanities and Medical Sciences, matrices belonging curriculum of undergraduate courses in Medicine in Brazil, considering the criteria for inclusion and exclusion. The study included 127 HEIs. The analysis of 7832 subjects showed that 22.8 % were humanistic disciplines. The state with the highest local rate of humanistic disciplines was Rio Grande do Norte, with 67.9% (n=129). Followed by Ceará with (51.6%, n=81) and Rondônia (32.4%, n=34). When subdivided by the five regions of the country, 27.86% concentrated in the Northeast, followed by the southern regions (23.15%, n=394), Southeast (22.26%, n=882), north (17.85%, n=96), and Midwest (17.37%, n=66). There was a negative correlation between the mortality rate and the IES (n), r = -0.414 (p <0.001). There was a significant correlation of the humanistic disciplines and the mortality rate (r = 0.933, p <0.001). The movements and reform initiatives in medical education in Brazil has led to debates about the health needs unmet and profiles of professionals who are in front of the health system. Especially with regard to medical education, much has been questioned regarding the technicalities profile of medical education offered by the institutions. The geographical, socioeconomic, cultural, climatic, ethnic make the Brazilian a complex panorama for taking resolute action scenario. Importantly, this diversity requires dynamic actions so that they can effectively reach all.